Higher Inequality Increases the Gap in the Perceived Merit of the Rich and Poor. (September 2017) - Heiserman, Nicholas; Simpson, Brent
The rewards people receive are often taken as indirect evidence of their merit. We outline an argument that addresses how the magnitude of macrolevel income inequalities affects perceptions of the distribution of merit in a society. We propose that higher levels of economic inequality will lead to perceptions of greater differences in merit such that societies with higher inequality will be characterized by a larger "merit gap, " namely, larger differences in the perceived merit of the rich and poor. We test these arguments using an online experiment that manipulated the level of inequality (high vs. low) in an anonymized society. Participants perceived a larger merit gap in high versus low inequality societies. Our arguments and findings have implications for attitudes about inequality and redistributive policies.